2022
DOI: 10.1097/01.aoa.0000816756.14706.2d
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal and Early Childhood Outcomes Following Maternal Anesthesia for Cesarean Section: A Population-based Cohort Study

Abstract: The material cannot be used for any other purpose without further permission of the publisher and is for private use only.There may be differences between this version and the published version. You are advised to consult the publisher's version if you wish to cite from it. http://eprints.gla.ac.uk/238521/ Deposited on

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…A cohort of 5320 children born between 1976 and 1982 showed no difference in learning disabilities between babies born by caesarean under regional compared with general anaesthesia compared with vaginal delivery [10]. More recently, a Scottish population‐based observational study of 140,866 children born between 2007 and 2016 found a weak association between general anaesthesia during delivery for caesarean birth and having ≥ 1 abnormality in childhood developmental assessment at age 2 y [11]. These studies clearly represent a different population receiving exposure to anaesthesia for only a short time during delivery and highlight the dearth of literature in this area [7].…”
Section: Existing Literaturementioning
confidence: 99%
“…A cohort of 5320 children born between 1976 and 1982 showed no difference in learning disabilities between babies born by caesarean under regional compared with general anaesthesia compared with vaginal delivery [10]. More recently, a Scottish population‐based observational study of 140,866 children born between 2007 and 2016 found a weak association between general anaesthesia during delivery for caesarean birth and having ≥ 1 abnormality in childhood developmental assessment at age 2 y [11]. These studies clearly represent a different population receiving exposure to anaesthesia for only a short time during delivery and highlight the dearth of literature in this area [7].…”
Section: Existing Literaturementioning
confidence: 99%